The Role of Cognitive Control in Age-Related Changes in Well-Being - Yagi, Ayano; Nouchi, Rui; Murayama, Kou; Sakaki, Michiko; Kawashima, Ryuta (Frontiers in Aging Neuroscience, 2020)
Maintaining emotional well-being in late life is crucial for achieving successful and healthy aging. While previous research from Western cultures has documented that emotional well-being improves as individuals get older, previous research provided mixed evidence on the effects of age on well-being in Eastern Asian cultures. However, previous studies in East Asia do not always take into account the effects of cognitive control – an ability which has been considered as a key to enable older adults to regulate their emotions. In the current study, we tested whether cognitive control abilities interact with age in determining individuals’ well-being in 59 Japanese females (age range: 26-79; Mage = 64.95). Participants’ mental health and mental fatigue were tracked for 5 years together with their cognitive control abilities. We found that as individuals became older, they showed improved mental health and decreased mental fatigue. In addition, for mental fatigue, we found a quadratic effect of age which was further qualified by baseline cognitive control abilities; in those who had a lower level of cognitive control abilities, mental fatigue declined until the mid 60s, at which point it started increasing (a U-shape effect). In contrast, in those who had a higher level of cognitive control ability, mental fatigue showed a steady decrease with age even after their mid-60s. These results suggest that whether advancing age is associated with positive vs. negative changes in well-being depends on cognitive control abilities and that preserved cognitive control is a key to maintain well-being in late life.